2022
DOI: 10.3390/en15165866
|View full text |Cite
|
Sign up to set email alerts
|

Combining the Water–Energy–Food and Food Waste–Food Loss–Food Security Nexuses to Reduce Resource Waste

Abstract: The availability of water, energy and food plays a key role in meeting the basic needs of the world population and allowing them to achieve prosperity and supports the UN’s sustainable development goals (SDGs). These three fundamental resources are closely interrelated, with their deep interdependencies reflected in various concepts of the ‘water–energy–food nexus’ (W–E–F). One-third of the total food produced globally results in food loss and waste (FL and FW), which also means the waste of resources used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The urgent need to reduce food loss and waste has been reported repeatedly (Béné et al., 2019; Skawińska & Zalewski, 2022; Springmann et al., 2018). A review of the various sources of food waste within food systems has identified 1.3–1.6 giga tons of food being wasted globally every year with enormous environmental, social, and economic costs and with impact on food security and material economics (Knorr & Augustin, 2022a).…”
Section: Future Food Processingmentioning
confidence: 98%
See 1 more Smart Citation
“…The urgent need to reduce food loss and waste has been reported repeatedly (Béné et al., 2019; Skawińska & Zalewski, 2022; Springmann et al., 2018). A review of the various sources of food waste within food systems has identified 1.3–1.6 giga tons of food being wasted globally every year with enormous environmental, social, and economic costs and with impact on food security and material economics (Knorr & Augustin, 2022a).…”
Section: Future Food Processingmentioning
confidence: 98%
“…An evaluation of the water−energy−food and food waste−food loss−food security nexuses to reduce food waste concluded that reducing food waste and loss has a positive effect on the water−energy−food nexus (Skawińska & Zalewski, 2022). Energy requirements for selected conventional and alternative food processes, some of the benefits of using low energy food processes and recommendations for food waste reduction, recovery and conversion via the collective work of all stakeholders within food systems have been provided (Knorr & Augustin, 2022a; Rodriguez‐Gonzalez et al., 2015).…”
Section: Future Food Processingmentioning
confidence: 99%
“…Indonesia's food waste emergency is a serious problem with multiple impacts: hunger and unsustainability [10]. Food wastage rates are high due to problems in the food supply chain, from farmers who have to throw away crops to consumers who often throw away food due to a lack of education.…”
Section: Food Waste Emergency Problemmentioning
confidence: 99%
“…The nexus of sustainable development, i.e., judicious use of water, energy, and food, determines the impacts on the environment. The global food system prioritises profit over social, health and environmental concerns, causing poor health, misspend water and energy, waste production, and loss of biological and cultural diversity, socio-economic exclusion, environmental degradation, and climate changes, through reduced emissions and enhanced soil carbon sequestration [87].…”
Section: Family Farmer's Business Sustainabilitymentioning
confidence: 99%